Impact of storage conditions on the shelf life of afatoxin biocontrol products containing atoxigenic isolates of Aspergillus favus as active ingredient applied in various countries in Africa - Ortega-Beltran, A.; Samuel Aikore, M.O.S.; Kaptoge, L.; Agbetiameh, D.; Moral, J; Bandyopadhyay, R. (Springer, 2024)
Aflatoxin contamination significantly threatens food safety and security, particularly in tropical and sub-tropical regions where staple crops such as maize, groundnut, and sorghum become frequently affected. This contamination is primarily caused by the fungus Aspergillus favus. The contamination causes adverse health effects, reduced income, and trade restrictions. In response to this challenge, various technologies have been developed to mitigate the impacts of aflatoxin. Among these, biocontrol products containing atoxigenic isolates of A. favus as the active ingredient can effectively reduce aflatoxin levels both at pre- and post-harvest. A notable example of such products is Afa safe, which contains four atoxigenic isolates native to specific target regions. These products have undergone rigorous testing, have received regulatory approval, and are commercially available in multiple African countries. However, their manufacturing processes have evolved, and comprehensive shelf-life studies for current formulations are lacking. Evaluations of the spore production ability of atoxigenic A. favus isolates in Afa safe products over 4 years, under various storage conditions, revealed a significant linear decrease in sporulation with storage months (P<0.001; R2=0.203), with no significant differences observed between treatments. However, this marginal decline (P=0.398) is unlikely to be sufficient to prevent the effectiveness in limiting aflatoxin. In addition, storing the products for 2 weeks at 54 °C did not affect (P>0.05) the ability of the coated fungi to produce spores compared to when the products were stored at 24 °C. The findings contribute valuable insights for manufacturers and users of atoxigenic based aflatoxin biocontrol products, informing best practices for product storage and utilization to ensure prolonged effectiveness in aflatoxin mitigation efforts.